The Reformation Era in Indonesia: Santri's Polarization and the Developmental Dynamics of Pesantren - Mustamar Iqbal (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
Since the fall of Suharto's regime in 1998, Indonesia has entered a new era of democracy dubbed the Reformation era. Religious ideology grew throughout this period, both locally and as a result of globalization. As a result, the polarization of students can no longer be read through classical or conventional typologies. The classic typology of students in the style of Clifford Geertz, followed by Yon Machmudi and Ahmad Najib Burhani's typology of students, also needs to represent the reality of students in the reform era fully. So, the literature study supported by interview data offers a new typology of santri divided into four forms, namely ideological, sociological, academic, and political santri. These four typologies color students’ polarization and impact the dynamics of Islamic boarding schools in Indonesia. However, this polarization in many cases experienced a